Contribution of Abbess Ekaterina (Efimovskaya) to the Revival of the Deaconesses Order in Russia - Parfyonova, Eugenia G. (Vestnik Svâto-Filaretovskogo instituta, 2023)
The article deals with the main concepts, ideas and practical measures for the revival of the ancient order of deaconesses in Russia in the late 19th — early 20th centuries taken by the abbess Ekaterina (Efimovskaya), the prioress of the Lesninsky Holy Mother of God Monastery. The author presents the main stages of the formation of the public and church service of Countess E. B. Efimovskaya and the prerequisites for her taking monastic vows. The author analyzes the church debate on “new monasticism”, which served as a justification for the missionary, educational and social activities of the Lesninsky Monastery, which was officially established in 1859. The memorandum by the abbess Ekaterina presented to the Holy Synod in 1905 is published in full for the first time. It contained proposals for the revival of the institute of deaconesses in Russia as well as the establishment of a community and a school of deaconesses on the basis of the Lesninsky monastery. The article considers the reception of these proposals by the church, which was positive in general, but was not followed by the official decision to establish the institute of deaconesses. However, the lack of the decision did not prevent Lesninsky Monastery sisters from continuing their activities. The author analyzes the features of ascetic practice and liturgical life, as well as the education policy and the principles of children upbringing in the monastery arranged according to the deaconesses service.